ANALISIS EFISIENSI USAHATANI JAGUNG PADA LAHAN KERING MELALUI PENERAPAN PENGELOLAAN TANAMAN TERPADU (PTT) DI PROVINSI JAWA BARAT - Silitonga, Parlindungan Y; Hartoyo, Sri; Sinaga, Bonar M; Rusastra, I Wayan (Sekretariat Badan Penelitian dan Pengembangan Pertanian, 2016)
Implementation of Integrated Crop Management (ICM) on maize farming in dry land is expected to increase the production and efficiency. This study aimed to: 1) analyze technical, allocative, and economic efficiencies of dry land maize farming under ICM and non-ICM implementation program, 2) identify factors that influence the technical inefficiency of maize farming under ICM and non-ICM implementation program. The study was conducted in maize production center in West Java province at Sukabumi and Garut regencies. Stratified random sampling method was used to survey 300 households in 2015. The data were analyzed using the Cobb-Douglas stochastic frontier production function; while allocative and economic efficiencies were analyzed using the input side approach with frontier dual cost function. The results showed that the productivity of ICM maize farming was 18% higher than the non-ICM. The level of technical, allocative and economic efficiencies of ICM maize farming were 88%, 22%, and 20% respectively, while the level of technical, allocative and economic efficiencies of non-ICM maize farming were 78%, 18%, and 14%, respectively. The level of technical, allocative and economic efficiencies increased by 11% to 30% higher in ICM than the non-ICM. Factors causing technical inefficiency were frequency of extension, educational level, and distance of farmland from farmers residence.